PENGEMBANGAN APLIKASI PENGOLAH NILAI BERBASIS WEB UNTUK MADRASAH TSANAWIYAH - Indra Sentosa; Dedi Irfan (Universitas Negeri Padang, 2019)
The change in the national education curriculum from the Kurikulum Tingkat Satuan Pendidikan to Kurikulum 2013 has brought changes to the assessment system. MTsN 1 Bukittinggi is one of the schools that applies Kurikulum 2013. The application of Kurikulum 2013 to this school also has an impact on changes in the assessment system. Changes to the grading system need to be supported by applications to facilitate processing of scores. At present, MTsN 1 Bukittinggi still uses a Spread Sheet-based score processing application. The applications used so far have been unable to meet the demands of the assessment system. With this Spread Sheet-based application, scores processing feels more complicated and still has the risk of input error. Therefore, it is necessary to develop a web-based scores application that is designed in accordance with the needs of the school. The purpose of this project is to develop a web-based scores processing application that can simplify the process of scores input, scores processing and study report printing. This application development uses the PHP programming language (PHP Hypertext Processor) with the CodeIgniter framework and MySQL as a Database Management System (DBMS). The system design method used is by Context Diagram, Flow Map, and Use Case Diagram. The results of the research is a web-based scores processing application that has been tested on several Internet browsers such as Mozilla Firefox and Google Chrome. The application runs well and can meet the needs of the school.Keywords: Score Processing Application, web, Spread Sheet, Madrasah Tsanawiyah